013 Has your work worked you too hard: an examination of work history, present functional limitations and reduced activities of living in a cohort of the Irish general population. (16th November 2010) - Mc Carthy, V J C; Perry, I J; Greiner, B A
Abstract : Objective: In the present paper, we examine the association between manual work, resultant functional limitations and reduced ability to carry out daily activities of living (ADL), in older age. We hypothesise that manual workers as opposed to non-manual workers suffer, in older age, functional limitations and reduced ability to carry out ADL. This study is of great importance owing to our ageing Irish population and an ailing health service. Methods: A 10 year follow up study was conducted on a cohort of the general population (59–80 year olds) in the Republic of Ireland. Specific data on physical measurements, marital status, educational attainment, work history, functional status and ADL was collected on 357 study participants. Work history data focused on the job the participant had done for the longest period of time, paid or unpaid. Each participant was then asked if they described this work as manual or non-manual. Functional limitations and ADL were assessed using validated scales. Results: Just over half the sample were female (53%) with 44% (n=150) retired (median=9 (5.14) years). Over 60% of the participants were, or had been engaged in manual work with this percentage higher in males, albeit non-significant (68% vs 58%, p=0.08). 20% of the total sample had complete function with a higher proportion of non-manual as opposed to manual workers (p=0.07) with no limitations. Almost three quarters of the sample had functional limitations and less than one fifth were classified as having an ADL disability. Using linear regression, manual workers were significantly more likely to have functional limitations even after adjustment (B=0.85, SE=0.30, p=0.01) for socio-demographic factors. When stratified by age, manual work remained significantly associated with functional limitations in the 60–69 year olds (B=0.66, SE=0.34, p=0.05) and in the 70–80 year olds (B=1.13, SE=0.50, p=0.03). For the older age group, males had a decreased risk of functional limitations independent of work type (B=−1.06, SE=0.47, p=0.03). There was no significant association between manual work and reduced activities of daily living either in the unadjusted or adjusted model. Discussion: Functional limitations, in an older population, are related to the type of work they carried out. Good health surveillance for manual workers at a young age can identify limitations early. Initiatives such as work organisation, education and promotion of best work practices with regard to manual work can reduce functional limitations in older age.